The Effect of the Empirical Base Nature of Science Learning Model on the Understanding of Nature of Science in Empirical Aspect - Duhita Savira Wardani; Ari Widodo; Ryan Dwi Puspita (Jurnal Pendidikan Indonesia, 2023)
Understanding of the nature of science, especially the empirical aspect, is now receiving less attention and seriousness from the educational community. The aim of this study was determine the effect of the Empirical Base Nature of Science (EBNOS) learning model on understanding NOS, especially on the empirical aspects of elementary school students. This study used a pre-experimental method through a one group pretest posttest design. The research subjects selected by convenience sampling were 51 students of class V of a private elementary school in the city of Bandung. The instrument used to collect data related to students' understanding of NOS at the pretest and posttest uses a Likert scale. Additional aspects explored from research subjects to support research results are aspects of gender and interest in science. Quantitative descriptive method with the help of SPSS and Microsoft Excel was used to analyze the data collected from the questionnaire. The results showed that the application of the Empirical Base Nature of Science (EBNOS) learning model design had a significant effect on increasing students' understanding of NoS, especially on the empirical aspect. However, understanding of the empirical aspect of NOS was not influenced by the gender of the students or their interest in science itself. This research is expected to contribute to the improvement of the learning process which aims to achieve science learning goals on the NOS dimension, especially on the empirical aspect. Suggestions for further research are developing specific learning models that can improve understanding of NOS in other aspects.